Pengaruh Pelajaran Pendidikan Kewarganegaraan terhadap Sikap Nasionalisme Siswa Kelas X SMK - Fifi Zuhriah (IKIP PGRI Bojonegoro, 2021)
Abstrak The purpose of this study is to know the influence of History-based Citizenship Education on students’ nationalism of Grade X of SMK. The research method used was duductive-inductive quantitative approach. This approach starts from a theoretical framework, the ideas of experts, as well as an understanding that is developed into problems to obtain justification (verification) through empirical data in the field. Through a sampling technique, the total of 14 students were involved. The data collection techniques used were observation and questionnaires about events related to students' nationalism attitudes, as well as multiple choice test instruments and descriptions of History-based Citizenship Education subjects. The technique of data analysis used was Product Moment and t-test. The results of the research based on the questionnaire showed that 55% of students' nationalism was in the good enough category. Based on observations, 71% have a high category of nationalism. While the statistical results show a positive and strong relationship of 0.969 and the alternative hypothesis is accepted at a significance level of 5%. The conclusion is that there is an influence of Citizenship Education lessons on nationalism attitudes in class X of SMK students. Keyword: Citizenship education, nationalism Abstrak Tujuan penelitian ini untuk mengetahui pengaruh pelajaran Pendidikan Kewarganegaraan yang berbasis sejarah terhadap sikap nasionalisme siswa Kelas X SMK. Metode penelitian yang digunakan kuantitatif [A1] dengan jenis penelitian menggunakan pendekatan deduktif-induktif. Pendekatan ini berangkat dari suatu kerangka teori, gagasan para ahli, maupun pemahaman yang dikembangkan menjadi permasalahan-permasalahan untuk memperoleh pembenaran (verifikasi) melalui data empiris di lapangan. Melalui teknik sampling total sebanyak 14 dengan teknik pengumpulan data melalui observasi dan angket tentang kejadian atau peristiwa berkaitan sikap Nasionalisme siswa, serta istrumen tes pilihan ganda dan uraian pada mata pelajaran Pendidikam Kewarganegaraan berbasis Sejarah. Analisis data dengan Product Moment dan Uji . Hasil penelitian berdasarkan angket menunjukkan sikap nasionalisme siswa sebesar masuk dalam kategori cukup baik. Berdasarkan observasi menunjukkan 71% mempunyai sikap nasionalisme yang berkategori tinggi. Sedangkan hasil statistik menunjukkan adanya hubungan yang positif dan kuat sebesar dan hipotesis Alternatif diterima pada taraf signifikansi Kesimpulan bahwa adanya pengaruh pelajaran Pendidikan Kewarganegaraan terhadap sikap nasionalisme pada siswa kelas X SMK. Kata kunci:Pendidikan Kewarganegaraan, Sikap Nasionalisme